2009
DOI: 10.1002/jor.20899
|View full text |Cite
|
Sign up to set email alerts
|

Medial knee joint loading increases in those who respond to hyaluronan injection for medial knee osteoarthritis

Abstract: Knee osteoarthritis (OA) is a cause of decline in function and the medial compartment is often affected. Intraarticular injection of hyaluronic acid (HA) is indicated as a symptom modifying treatment with at least 6 months passing between consecutive injection series. The effects of HA injection on gait variables have not been extensively examined. Therefore, our objective was to investigate the effects of HA injection on gait in people with medial knee OA. Twenty-seven subjects were included; each was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
0
31
2
1
Order By: Relevance
“…The study with the longest follow-up duration reported that analgesic use had no impact on PCS or MCS through 1 year of use [36]. Regular use of these agents has no impact on disease progression and, in fact, they may accelerate OA progression due to higher resulting forces across the knee joint [37-40]. Therefore, their long-term benefit on HRQoL is doubtful.…”
Section: Effect Of Nonsurgical Interventions On Hrqolmentioning
confidence: 99%
See 1 more Smart Citation
“…The study with the longest follow-up duration reported that analgesic use had no impact on PCS or MCS through 1 year of use [36]. Regular use of these agents has no impact on disease progression and, in fact, they may accelerate OA progression due to higher resulting forces across the knee joint [37-40]. Therefore, their long-term benefit on HRQoL is doubtful.…”
Section: Effect Of Nonsurgical Interventions On Hrqolmentioning
confidence: 99%
“…Additionally, the changes in functional pain scores with viscosupplementation do not correlate to quality of life scores [50]. Similar to findings with acetaminophen and NSAIDS, hyaluronic acid injections may actually increase knee joint loading and accelerate joint deterioration due to short-term pain amelioration [37]. Finally, the safety of HA injections has recently been questioned [52].…”
Section: Effect Of Nonsurgical Interventions On Hrqolmentioning
confidence: 99%
“…Although pharmacological therapy improves knee OA symptoms in many cases, no nonsurgical treatment has been shown to slow disease progression 3 . Paradoxically, conservative therapies may actually encourage OA progression in responders since patients may become more physically active, leading to higher peak adduction moments across the knee joint 4-7 . Over 80% of orthopedic surgeons agreed that better treatment alternatives are needed in younger OA patients in which arthroplasty is not indicated, and over 2 in 3 perceived a treatment gap for early knee OA 8 .…”
Section: Early Knee Osteoarthritis Managementmentioning
confidence: 99%
“…In healthy subjects, experimentally induced knee pain has been shown to replicate altered gait-movement strategies seen in patients with mild knee OA (that is, reduced first peak KAM and sagittal plane moments were seen) [38]. Studies have shown that pharmacologically initiated pain relief in knee OA is associated with increased loads in KAM and sagittal knee moments [12, 17, 32, 39, 40]. Therefore, pharmacologic pain relief, by eliminating the protective mechanism of the pain itself may be detrimental for knee-joint structures by increasing knee-joint load.…”
Section: Introductionmentioning
confidence: 99%